Riglyne vir die implementering van 'n eienaar-drywerstelsel - J. S. Spamer; W. J. Pienaar (South African Journal of Business Management, 1998)
– Guidelines for the implementation of an owner-driver scheme.The aim of this article is to supply guidelines for the implementation of an owner-driver scheme. Such implementation is the outsourcing of a firm's transport obligations to vehicle owner-drivers who are not employees of the firm. In most cases these individuals are ex-employees of the firm who are now acting as independent hauliers. The objectives of an owner-driver scheme and the different forms which such a scheme can adopt, are briefly outlined. Thereafter the criteria for implementation, and also the critical success factors of such a scheme. are discussed. It is pointed out that the firm will have to decide whose responsibility it is to initially manage the scheme. This decision, combined with the contract, the method of financing and the renumeration system, determine the nature of an owner-driver scheme. Firms wishing to implement an owner-driver scheme should approach it in a structured manner within a well-considered implementation programme. Implementation of the owner-driver scheme is discussed according to six phases, namely: (I) initiation, (2) evaluation, (3) planning, (4) contracting, (5) transition, and (6) management and review.
Keywords: 650